Buoyancy studies of three morphs of the Antarctic fish Trematomus newnesi (Nototheniidae) from the South Shetland Islands - Eastman, Joseph T.; Barrera Oro, Esteban (Polar Biology)
Phenotypic plasticity, a widespread phenomenon in boreal freshwater fishes, is less apparent in the marine realm and the organism-environment interactions producing this variation are undetermined. A sample of 40 specimens of Trematomus newnesi, an inshore Antarctic fish from King George/25 de Mayo Island in the South Shetlands, was composed of 52.5% typical morphs, 27.5% large-mouth morphs and 20% intermediate morphs. Measurements of percentage buoyancy on the morphs of this sample were 3.73, 3.84 and 3.83%, respectively with no significant differences among means. Both mean dry skeletal weight as a percentage of body weight and mean oral jaw weight as a percentage of dry skeletal weight were significantly greater in large-mouth morphs compared to typical morphs. Diversification in head and jaw morphology is not accompanied by diversification in ecology as represented by buoyancy and, in spite of external appearances, measurements of buoyancy offer no support for the hypothesis that the large-mouth morph is more benthic than the typical semipelagic morph. Although a trophic basis for this polymorphism is possible, it has not yet been documented. Our discussion centers on the status of key open questions regarding morphism and highlights areas requiring more research. Fil: Eastman, Joseph T. Ohio University; Estados Unidos Fil: Barrera Oro, Esteban. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina